The Influence of Akhmet Baitursynov’s Literary Publicistic Heritage on The Spiritual Development of Kazakh People at The Beginning of The XXth Century - Dossanova, Nazira; Abdimanuly, Omirkhan; Kapağan, Enver (Journal of History Culture and Art Research, 2020)
The article examines multifaceted activities of an outstanding Kazakh poet and publicist of the early twentieth century, Akhmet Baitursynov, and his transformative role in the development of literature, as well as national press and the history of the liberation movement. Authors especially emphasize that the poet and enlightener A. Baitursynov, as a creative person, has completely devoted himself to serving the people and their struggle for independence. In the process of analyzing the poet’s work, it was shown that his bright poetry and social activities, as in a mirror, reflected the history of his native people at a turning point in the social changes of the twentieth century. Rich historical, literary and artistic material reveals the influence of Russian classical literature on the work of the Kazakh poet. The degree of artistic perception and adaptation techniques used by A. Baitursynov on I. A. Krylov’s fables are revealed. The peculiar method and artistic skill of A. Baitursynov as a translator are considered in the given article. As an original fabulist, he uses words, expressions, proverbs and sayings that are close to and understandable to Kazakh people. He focuses on their critical and satirical orientation, which is aimed not to entertain, but to correct morals, teaching, and appeal to education. A. Baitursynov’s special place in the history of the national press was identified as a talented publicist and bold editor of the Kazakh newspaper, which had a pronounced anti-colonial and enlightening orientation. His journalistic legacy was deeply investigated and systematically analyzed. The authors proved that it was in the field of the Kazakh press that the poet’s powerful talent was most fully revealed, his role as the leader and inspirer of the liberation struggle of the Kazakh people was investigated.